Método quantitativo para a avaliação de impactos ambientais aplicado à indústria têxtil - Duarte, Paulo Henrique Girão (2006)
The increasing concerning about environmental matters, added to the necessity of promoting sustainable development, transformed the discussion about evaluation and reduction of environmental impacts, related to industrial activities, in an emergent issue. Several methods currently applied to evaluate environmental impacts, for various types of enterprises, have considerable subjectivity. The objective of this work is to achieve the development of a quantitative method for the evaluation of environmental impacts; hence there are few scientific studies in this subject, mainly in Ceara State. The method developed allows the application of environmental indicators, divided in category sets. Mathematical functions are associated to these indicators in order to obtain non-dimensional values called environmental quality indexes. These indexes are combined using arithmetical means until the determination of a unique numerical value, which is representative of the organization’s environmental performance. Practical application of the method was conducted in a textile industry, in which were elected 18 indicators, grouped in three categories: resources efficiency, effluents and gas emissions. Obtained results show good effectiveness of the method concerning to the industrial intrinsic process variations, giving environmental managers the possibility of making fact based decisions, in a simple way and with significant reduction of the subjectivity related to the analysis of the environmental impacts considered